Sintesis Zeolit 4A Menggunakan Abu Limbah Sawit Variasi NaOH Sebagai Pelebur Serta Variasi Volume Natrium Silikat Dan Natrium Aluminat - Mimin lestari; Fajril Akbar; Silvia Reni Yenti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Zeolite 4A is one of synthetic zeolite which is used as ion exchange. This zeolite can be synthesized from silica and alumina. In this reaearch , palm ash used as a source of silica. The aims of this research is produce zeolite 4A using palm ash and obtain the optimum process condition of synthesis zeolite 4A. The fusion of palm ash was done in furnace at temperature 500 ᴼC for 5 minutes with various of palm ash:NaOH (25:30 , 25:50 and 25:75 gram/gram). Synthesis perfomed with variation of ratio volume sodium silicate and sodium aluminate (55:45, 60:40 and 65:35 mL/mL). The product was characterized using spectrophotometry fourier transform infra red (FTIR) and X ray diffraction (XRD). Based on the result of characterization, the terbaik process condition was obtained at each variation that is the fusion of palm ash at ratio palm ash:NaOH 25:30 gram/gram and ratio volume sodium silicate and sodium aluminate 65:35 mL/mL.Keyword : palm ash, spectrophotometry FTIR, XRD, zeolite 4A